Estudo da obtenção de compósitos alumínio/quasicristal via sinterização por superaquecimento - Gonzaga, Maria Aline Martins (2019)
The continuous requirement of light and high performance materials for the aerospace and automotive industries led to the development of composite materials with metallic matrix (MMC). The most popular types of MMC are aluminum alloys reinforced with ceramic particles; however, metallic reinforcing particles of quasicrystals have been gaining space due to the low cost, easy access, recyclability and non-toxicity of the components, as well as providing comparable properties or even better than existing ceramic reinforced MMC. This work aims to develop a new process that allows the formation of aluminum matrix composites with the addition of quasicrystalline particles reinforcement. To obtain the composites, the powder metallurgy technique was used in combination with a new sintering route of the aluminum and quasicrystal powders, through a liquid metal bath. Micrometric quasicrystalline particles of the Al62.2Cu25.5Fe12.3 alloy were introduced, in the volume proportions of 2.5%, 5% and 10%, in an aluminum matrix. The quasicrystalline alloy was obtained by melting and heat treated for 8h at 750°C. Then, cold compacts were produced from the composites and placed in a heated steel mold, thereafter receiving a molten recycled aluminum bath in order to promote sintering. Through the new processing route used, it was possible to obtain sintered Al/QC compacts, resulting in composites with a good distribution of the quasicrystalline particles in the aluminum matrix. The large size distribution of reinforcing particles promoted the formation of pore and agglomerate regions. It was possible to observe the tendency of the increase of the hardness of the sintered composites with the increase of the volumetric fraction of the quasicrystalline reinforcement in the aluminum matrix.